Preparation method of self-assembled monomolecular layer in perovskite battery

By using high boiling point solvent to prepare SAM precursor and quickly immerse the conductive glass substrate, the uniformity and speed of SAM layer preparation in perovskite batteries are solved, and efficient and stable perovskite battery preparation is achieved, which improves the conversion efficiency and Stability, suitable for large-area batteries.

CN119136623AInactive Publication Date: 2024-12-13WUXI YONGJIA LIGHT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 10 Cited by

Patent Information

Application Number
CN202411273757.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The preparation method of self-assembled single-molecular layer in existing perovskite batteries has problems such as difficulty in ensuring uniformity, large waste of materials, and slow preparation speed. It is especially difficult to achieve rapid, high throughput, and material usage when preparing large-area modules. Less uniformly dense SAM layer.

Method used

The SAM precursor liquid is prepared by using a high boiling point solvent. The SAM precursor liquid is quickly immersed in the preheated SAM precursor liquid and completed the self-assembly at high temperatures. The residual solvent is then removed and annealed to achieve uniform and dense preparation of the SAM layer.

Benefits of technology

It significantly improves the conversion efficiency and stability of perovskite batteries, shortens the preparation time by dozens of times, is suitable for large-area batteries, saves raw materials, and has industrial potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136623A_ABST
    Figure CN119136623A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a self-assembled monomolecular layer in a perovskite cell, and belongs to the technical field of solar cells, and the preparation method comprises the following steps: S1, preparing an SAM layer; step S1.1, soaking the conductive glass substrate into the preheated SAM first precursor solution; step S1.2, quickly soaking in a second SAM precursor solution; s1.3, taking out and removing the residual solvent to obtain an SAM layer; step S2, annealing; s3, preparing a perovskite light absorption layer and other functional layers; and depositing a perovskite light absorption layer and other functional layers on the SAM layer in sequence, and finally preparing a complete perovskite solar cell. According to the method, the appropriate high-boiling-point solvent is selected to prepare the SAM precursor solution, then the conductive substrate is rapidly soaked in the SAM precursor solution under the condition that the high temperature is kept, SAM molecules are rapidly self-assembled within seconds at the high temperature, the self-assembled molecular layer is more uniform and compact, the perovskite buried bottom interface has fewer defects, the interface contact is better, and the performance of the conductive substrate is improved. And the efficiency and the stability of the perovskite cell are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a self-assembled monomolecular layer in a perovskite battery, and belongs to the technical field of solar cells. Background Art

[0002] Organic-inorganic hybrid lead halide perovskite cells (PSCs) have rapidly become the leader in the new generation of photovoltaic technology due to their high efficiency, huge cost reduction potential, widely adjustable bandwidth gap and extremely wide application scenarios.

[0003] PIN-type cells are leading in the industrialization of perovskite photovoltaics due to their simpler device structure. An important part of this is the buried interface material between the perovskite and the conductive substrate. Currently, the most commonly used and most efficient self-assembled single molecule (SAM) material in the industry is a small molecule containing a phosphate group, such as [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz). This layer plays an important role in collecting photogenerated holes and inhibiting the recombination of buried interface carriers, and also has an important influence on the growth of the perovskite light-absorbing layer. The most commonly used method for preparing this layer is to dissolve SAM materials such as MeO-2PACz in methanol or ethanol, then spin-coat it on the bottom substrate and anneal it. However, the spin coating method is not applicable when preparing large-area modules. First, uniformity is difficult to guarantee, second, material waste is extremely large, and third, the preparation speed is very slow, which will seriously limit production capacity.

[0004] On the other hand, this type of SAM molecule cannot be made using methods such as evaporation, and due to its extremely thin thickness, the preparation accuracy of the slit coating method cannot be met.

[0005] Therefore, developing a fast, high-throughput, and low-material method to achieve a uniform and dense SAM layer is an urgent problem to be solved in the field of perovskite photovoltaics for successful industrialization. Summary of the invention

[0006] The technical problem to be solved by the present invention is: in order to overcome the shortcomings of the prior art, a method for preparing a self-assembled monolayer in a perovskite cell is provided which can achieve a uniform and dense SAM layer quickly, with high throughput and low material usage.

[0007] The method described can prepare a uniform and dense SAM layer on an unlimited area and unlimited number of conductive glass substrates within a dozen seconds, and has been successfully applied to perovskite solar cell devices. The conversion efficiency and stability of perovskite cells prepared by the traditional spin coating method for SAM layer have been significantly improved.

[0008] The technical solution adopted by the present invention to solve the above problem is: a method for preparing a self-assembled monolayer in a perovskite battery, comprising the following steps:

[0009] Step S1, preparing a SAM layer;

[0010] Step S1.1, immersing the conductive glass substrate into the preheated SAM first precursor solution;

[0011] Step S1.2, quickly immersing in the second SAM precursor solution;

[0012] Step S1.3, taking out and removing the residual solvent to obtain a SAM layer;

[0013] Step S2, annealing;

[0014] Step S3, preparing a perovskite light absorbing layer and other functional layers;

[0015] Sequentially depositing a perovskite light-absorbing layer and other functional layers on the SAM layer to ultimately prepare a complete perovskite solar cell;

[0016] The solvents of the first SAM precursor liquid and the second SAM precursor liquid are both high boiling point solvents;

[0017] The perovskite light-absorbing layer is any organic-inorganic metal halogen hybrid perovskite light-absorbing material;

[0018] The other functional layers include a perovskite surface passivation layer, an electron transport layer, an interface modification layer and an electrode.

[0019] Preferably, the raw materials of the first SAM precursor solution and the second SAM precursor solution are both small molecule materials having a phosphate group and a function of modifying the perovskite / conductive substrate interface, including but not limited to MeO-2PACz, [3-(3,6-dimethoxy-9H-carbazole-9-yl)propyl]phosphoric acid (MeO-3PACz), [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphoric acid (MeO-6PACz), [2-(3,6-dimethyl-9H-carbazol-9-yl)ethyl]phosphoric acid (Me-2PACz), [3-(3,6-dimethyl-9H-carbazol-9-yl)propyl]phosphoric acid (Me-3PACz), [6-(3,6-dimethyl-9H-carbazol-9-yl)hexyl]phosphoric acid (Me-6PACz), [1-(3,6-dimethyl-9H-carbazol-9-yl)methyl]phosphoric acid (Me-1PACz), [4 ...6-dimethyl-9H-carbazol-9-yl)butyl] phosphate (Me-4PACz), [8-(3,6-dimethyl-9H-carbazol-9-yl)octyl] phosphate (Me-8PACz), [1-(9H-carbazol-9-yl)methyl] phosphate (1PACz), (2-(9H-carbazol-9-yl)ethyl) phosphate (2PACz), [3-(9H-carbazol-9-yl)propyl] phosphate (3PACz), [4-(9H-carbazol-9-yl)butyl] phosphate (4PACz), [6-(9H-carbazol-9-yl)hexyl] phosphate (6PACz), [8-(9H-carbazol-9-yl)octyl] phosphate (8PACz), [4-(N,N-di(4-methyl) [4-(diphenylamino)phenyl)propyl] phosphate (TPA-2PA), [4-(diphenylamino)phenyl)propyl] phosphate (TPA-3PA), [4-(10H-phenothiazine-10-yl)butyl] phosphate (4PAPT), [2-(7H-dibenzocarbazole-7-yl)ethyl] phosphate (2PABCz), [4-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)butyl] phosphate (4PABCz), [4-(diphenylamino)phenyl)ethyl] phosphate (TPA-2PA), [4-(diphenylamino)phenyl)propyl] phosphate (TPA-3PA), [4-(10H-phenothiazine-10-yl)butyl] phosphate (4PAPT), [2-(7H-dibenzocarbazole-7-yl)ethyl] phosphate (2 PADCB), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid (4PADCB), [3-(3,6-dibromo-9H-carbazole-9-yl)propyl]phosphoric acid (2Br-3PACz), [4-(3,6-dibromo-9H-carbazole-9-yl)butyl]phosphoric acid (2Br-4PACz), [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphoric acid (2Br-6PACz), [1-(3,6-di-tert-butyl-9H-carbazole-9-yl)methyl]phosphoric acid (tBu-1PACz), [2-(3,6-di-tert-butyl-9H-carbazole-9-yl)ethyl]phosphoric acid (tBu-2PACz), [3-(3,6-di-tert-butyl- 9H-carbazol-9-yl)propyl] phosphate (tBu-3PACz), [4-(3,6-di-tert-butyl-9H-carbazol-9-yl)butyl] phosphate (tBu-4PACz), [6-(3,6-di-tert-butyl-9H-carbazol-9-yl)hexyl] phosphate (tBu-6PACz), [8-(3,6-di-tert-butyl-9H-carbazol-9-yl)octyl] phosphate (tBu-8PACz), [1-(3,6-diphenyl-9H-carbazol-9-yl)methyl] phosphate (Ph-1PACz), [2-(3,6-diphenyl-9H-carbazol-9-yl)ethyl] phosphate (Ph-2PACz), [3-(3,6-diphenyl-9H-carbazol-9-yl),

[0020] [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl] phosphate (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl] phosphate (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl] phosphate (Ph-8PACz), [2-(10H-phenoxazine-10-yl)ethyl] phosphate (2PAPXZ), [4-(3,7-dibromo-10H-phenothiazine-10-yl)butyl] phosphate (2Br-4PAPT), [4-(3,7-dibromo-10H-phenoxazine-10-yl)butyl] phosphate (2Br-4PAPXZ) and a series of phosphate molecules.

[0021] Preferably, the solvents of the first SAM precursor solution and the second SAM precursor solution are both solvents with polarity>3.0, including but not limited to isobutanol, n-butanol, butyl acetate, propanol, methyl isobutyl ketone, tetrahydrofuran, ethyl acetate, isopropanol, chloroform, methyl ethyl ketone, dioxane, pyridine, acetone, nitromethane, acetic acid, acetonitrile, aniline, dimethylformamide, methanol, ethylene glycol, dimethyl sulfoxide, ethanol, butyrolactone, water, etc. The solvents of the first SAM precursor solution and the second SAM precursor solution also include a combination of any type and ratio of two or more of the above solvents.

[0022] Preferably, the concentration range of the SAM first precursor solution is 1 ug / mL-1000 ug / mL, and the concentration range of the SAM second precursor solution is 1 ug / mL-100 ug / mL;

[0023] The temperature of the first SAM precursor liquid is 60°C-300°C, and the temperature of the second SAM precursor liquid is 0°C-200°C.

[0024] Preferably, the conductive glass substrate is immersed in the first SAM precursor solution for 0.5 seconds to 300 seconds, immersed in the second SAM precursor solution for 5 seconds to 1800 seconds, and the time for transferring from the first SAM precursor solution to the second SAM precursor solution is <2 seconds.

[0025] Preferably, the conductive glass substrate is taken out from the second precursor solution to remove residual solvent, and the methods for removing the residual solvent include but are not limited to strong blowing with nitrogen, blowing with argon, blowing with dry compressed air, blowing with carbon dioxide gas, drying with infrared lamp, vacuum drying, etc.

[0026] Preferably, after the conductive glass is taken out from the second precursor solution, residual solvent is removed and annealed. The annealing temperature is 80° C.-200° C., the annealing time is 1 minute-30 minutes, and the annealing environment is in air environment or in a glove box protected by inert gas.

[0027] Preferably, the perovskite light absorbing layer and other functional layers are deposited on the SAM layer at one time, and the methods of depositing the perovskite and other functional layers include but are not limited to spin coating, scraping, slit coating, screen printing, thermal evaporation, ion beam deposition, magnetron sputtering deposition, atomic layer deposition, etc.

[0028] Preferably, the material of the perovskite light absorbing layer has a general structural formula of ABX3;

[0029] Wherein, A is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following:

[0030] B is selected from Pb 2+ ,Ge 2+ Sn 2+ Any one or a combination of at least two of the following:

[0031] X is selected from Cl - Br - or I - Any one or a combination of at least two of the following:

[0032] The thickness of the perovskite light absorbing layer is 200nm to 1500nm;

[0033] The perovskite cell types include single-cell perovskite solar cells and also include the hole collection layer of the broadband perovskite part in the perovskite / crystalline silicon stacked solar cell.

[0034] Preferably, the perovskite cell type includes perovskite / perovskite tandem solar cells, which serve as hole transport layers for wide bandgap and narrow bandgap cells, respectively.

[0035] Compared with the prior art, the advantages of the present invention are:

[0036] The present invention discloses a method for preparing a self-assembled monolayer in a perovskite battery. The method comprises the following steps: selecting a suitable high-boiling point solvent to prepare a SAM precursor solution, and then rapidly immersing a conductive substrate in the precursor solution while maintaining a high temperature (temperature near the boiling point of the solvent). The SAM molecules rapidly complete self-assembly within a few seconds at the high temperature. The self-assembled molecular layer is more uniform and dense, resulting in fewer interface defects at the buried perovskite bottom and better interface contact. The efficiency and stability of the perovskite battery are significantly improved. More importantly, the preparation speed of the method is increased by dozens of times, and the method can be applied to large-area batteries at a high throughput, and raw materials are more saved. The present invention is of great significance to the industrialization of PIN-type perovskite photovoltaic technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a flow chart of a method for preparing a self-assembled monolayer in a perovskite battery according to the present invention;

[0038] Figure 2 The SAM layer is grown in situ by the rapid immersion method at different temperatures and the corresponding perovskite cell conversion efficiency diagram when the SAM solvents in the present invention are butyrolactone (Example 1), DMF (Example 2), and n-butanol (Example 3);

[0039] Figure 3 The SAM layer grown in situ by the rapid immersion method (under optimal conditions (Example 4)) in the present invention is compared with the SAM layer prepared by the conventional spin coating method (Example 5), and they are applied to complete perovskite cells, and the statistical data comparison diagrams of their Voc, Jsc, FF and PCE are obtained;

[0040] Figure 4 The JV curves of the optimal efficiency cells obtained by the SAM layer in situ grown by the rapid immersion method (Example 4) and the SAM layer prepared by the traditional spin coating method (Example 5) in the present invention are compared.

[0041] Figure 5 Graph showing the long-range stability data of the optimal stability battery obtained by the SAM layer in situ grown by the rapid immersion method (Example 4) and the SAM layer prepared by the traditional spin coating method (Example 5) in the present invention (the packaged battery is preserved in the open circuit voltage state at room temperature in the dark). DETAILED DESCRIPTION

[0042] like Figure 1-5 As shown, a method for preparing a self-assembled monolayer in a perovskite battery in this embodiment, wherein the hole collection layer of the perovskite battery is a SAM layer, and the specific preparation steps are as follows:

[0043] Step S1, preparing a SAM layer;

[0044] Step S1.1, immersing the cleaned transparent conductive glass substrate into the preheated SAM first precursor solution;

[0045] Step S1.2, quickly immersing in the second SAM precursor solution;

[0046] Step S1.3, taking out and removing the residual solvent to obtain a SAM layer;

[0047] Step S2, annealing;

[0048] Step S3, preparing a perovskite light absorbing layer and other functional layers;

[0049] Sequentially depositing a perovskite light-absorbing layer and other functional layers on the SAM layer to ultimately prepare a complete perovskite solar cell;

[0050] In the present invention, the raw materials of the first SAM precursor solution and the second SAM precursor solution are both ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz)), but may also include [3-(3,6-dimethoxy-9H-carbazole-9-yl)propyl]phosphoric acid (MeO-3PACz), [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphoric acid (MeO-6PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphoric acid (Me-2PACz), [3-(3,6-dimethyl-9H-carbazole-9-yl)propyl]phosphoric acid (Me ... 6-dimethyl-9H-carbazol-9-yl)hexyl] phosphate (Me-6PACz), [1-(3,6-dimethyl-9H-carbazol-9-yl)methyl] phosphate (Me-1PACz), [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl] phosphate (Me-4PACz), [8-(3,6-dimethyl-9H-carbazol-9-yl)octyl] phosphate (Me-8PACz), [1-(9H-carbazol-9-yl)methyl] phosphate (1PACz), (2-(9H-carbazol-9-yl)ethyl) phosphate (2PACz), [3-(9H-carbazol-9-yl)propyl] phosphate (3PACz), [4-(9H-carbazol-9-yl)butyl] phosphate (Me-4PACz), [8-(3,6-dimethyl-9H-carbazol-9-yl)octyl] phosphate (Me-8PACz), [1-(9H-carbazol-9-yl)methyl] phosphate (1PACz), (2-(9H-carbazol-9-yl)ethyl) phosphate (2PACz), [3-(9H-carbazol-9-yl)propyl] phosphate (3PACz), [4-(9H-carbazol-9-yl) butyl] phosphate (4PACz), [6-(9H-carbazole-9-yl)hexyl] phosphate (6PACz), [8-(9H-carbazole-9-yl)octyl] phosphate (8PACz), [4-(N,N-di(4-methoxyphenylamino)phenyl)propyl] phosphate (MeO-TPA-3PA), 2,3,4,5,6-pentafluorobenzyl phosphate (F5BPA), [2-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)ethyl] phosphate (2PABCz), [4-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)butyl] phosphate (4PABCz), [4-(diphenylamino)phenyl)ethyl] phosphate (TPA-2PA ), [4-(diphenylamino)phenyl)propyl]phosphoric acid (TPA-3PA), [4-(10H-phenothiazine-10-yl)butyl]phosphoric acid (4PAPT), [2-(7H-dibenzocarbazole-7-yl)ethyl]phosphoric acid (2PADCB), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid (4PADCB), [3-(3,6-dibromo-9H-carbazole-9-yl)propyl]phosphoric acid (2Br-3PACz), [4-(3,6-dibromo-9H-carbazole-9-yl)butyl]phosphoric acid (2Br-4PACz), [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphoric acid (2Br-6PACz), [1-(3,[6-di-tert-butyl-9H-carbazole-9-yl)methyl]phosphoric acid (tBu-1PACz), [2-(3,6-di-tert-butyl-9H-carbazole-9-yl)ethyl]phosphoric acid (tBu-2PACz), [3-(3,6-di-tert-butyl-9H-carbazole-9-yl)propyl]phosphoric acid (tBu-3PACz), [4-(3,6-di-tert-butyl-9H-carbazole-9-yl)butyl]phosphoric acid (tBu-4PACz), [6-(3 ,6-di-tert-butyl-9H-carbazole-9-yl)hexyl] phosphate (tBu-6PACz), [8-(3,6-di-tert-butyl-9H-carbazole-9-yl)octyl] phosphate (tBu-8PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl] phosphate (Ph-1PACz), [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl] phosphate (Ph-2PACz), [3-(3,6-diphenyl-9H-carbazole-9-yl)ethyl] phosphate (Ph-4PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl] phosphate (Ph-2PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)ethyl] phosphate (Ph-3PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)octyl] phosphate (Ph-4PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl] phosphate (Ph-1PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)octyl] phosphate (Ph-3 ... [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphoric acid (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl]phosphoric acid (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl]phosphoric acid (Ph-8PACz), [2-(10H-phenoxazine-10- [4-(3,7-dibromo-10H-phenothiazine-10-yl)butyl]phosphoric acid (2Br-4PAPT), [4-(3,7-dibromo-10H-phenothiazine-10-yl)butyl]phosphoric acid (2Br-4PAPXZ) and a series of phosphate molecules, the solvent of the first SAM precursor solution and the second SAM precursor solution also include any combination of two or more of the above solvents in any type and ratio;

[0051] In the present invention, the solvents of the first SAM precursor solution and the second SAM precursor solution are both solvents with polarity>3.0, including but not limited to isobutyl alcohol, n-butyl alcohol, butyl acetate, propanol, methyl isobutyl ketone, tetrahydrofuran, ethyl acetate, isopropanol, chloroform, methyl ethyl ketone, dioxane, pyridine, acetone, nitromethane, acetic acid, acetonitrile, aniline, dimethylformamide, methanol, ethylene glycol, dimethyl sulfoxide, ethanol, butyrolactone, water, etc.:

[0052] In the present invention, the concentration range of the SAM first precursor solution is 1 ug / mL-1000 ug / mL, and the concentration range of the SAM second precursor solution is 1 ug / mL-100 ug / mL;

[0053] In the present invention, the temperature of the first SAM precursor solution is 60°C-300°C, and the temperature range of the second SAM precursor solution is 0°C-200°C;

[0054] In the present invention, the soaking time of the conductive glass substrate in the first precursor solution of SAM is 0.5 seconds to 300 seconds, the soaking time of the conductive glass substrate in the second precursor solution of SAM is 5 seconds to 1800 seconds, and the time for transferring from the first precursor solution of SAM to the second precursor solution is <2 seconds;

[0055] In the present invention, after the conductive glass substrate is taken out from the second precursor solution, the residual solvent is quickly removed, and the methods for removing the residual solvent include but are not limited to strong blowing dry with nitrogen, blowing dry with argon, blowing dry with dry compressed air, blowing dry with carbon dioxide gas, drying with an infrared lamp, drying by a vacuum method, etc.;

[0056] In the present invention, the annealing temperature of the SAM layer is 80 °C to 200 °C, the annealing time is 1 minute to 30 minutes, and the annealing environment is in an air environment or in a glove box protected by an inert gas;

[0057] In the present invention, the thickness of the SAM layer is 0.1 nm to 5 nm;

[0058] In the present invention, the conductive substrate includes FTO glass, ITO glass, AZO glass, transparent silver nanowire glass, transparent copper nanowire glass, transparent polyaniline glass, and flexible transparent substrates, etc.:

[0059] In the second aspect, in the present invention, the perovskite light-absorbing layer material of the perovskite solar cell includes MAPbI3, FAPbI3, MA x FA (1-x) PbI3(0 < x < 1), Cs x MA y FA z PbI3(x + y + z = 1), the band gap ranges from 1.49 to 1.75 eV, and the thickness ranges from 400 to 1000 nm;

[0060] In the present invention, the perovskite light-absorbing layer material of the perovskite solar cell may also include wide-bandgap perovskite, the band gap ranges from, including Cs x MA y FA z PbI 3-n Br n (x + y + z = 1, 0 < n < 3), and the thickness ranges from 200 nm to 1000 nm;

[0061] In the present invention, the perovskite light-absorbing layer material of the perovskite solar cell may also include narrow-bandgap perovskite, the band gap ranges from, including Cs x MA y FA z SnPb nI3(x + y + z = 1, 0 < n < 3), with a thickness range of 500 nm - 2000 nm;

[0062] In the present invention, the deposition methods of the perovskite and other functional layers include, but are not limited to, spin coating, blade coating, slot die coating, screen printing, thermal evaporation, ion beam deposition, magnetron sputtering deposition, atomic layer deposition, etc.

[0063] In the third aspect, in the present invention, the perovskite solar cells using the SAM layer prepared by the method not only include the single - cell of various different perovskites described in the second aspect, but also include the HTL part of the wide - bandgap cell in the all - perovskite tandem cell. The structure of the all - perovskite tandem cell is conductive glass / SAM layer / wide - bandgap perovskite / electron transport layer / intermediate layer / hole transport layer / narrow - bandgap perovskite light - absorbing layer / electron transport layer / electrode;

[0064] In the present invention, the SAM layer prepared by the method also includes the HTL part of the narrow - bandgap cell in the all - perovskite tandem cell. The structure of the all - perovskite tandem cell is conductive glass / hole transport layer / wide - bandgap perovskite / electron transport layer / intermediate layer / SAM layer / narrow - bandgap perovskite light - absorbing layer / electron transport layer / electrode.

[0065] In the fourth aspect, in the present invention, the perovskite solar cells using the SAM layer prepared by the method not only include the cells described in the first and second aspects, but also include the HTL part of the wide - bandgap cell in the perovskite / crystalline silicon tandem cell. The structure of the all - perovskite tandem cell is crystalline silicon cell / intermediate layer / SAM layer / wide - bandgap perovskite / electron transport layer / electrode;

[0066] Example 1

[0067] This example provides a perovskite solar cell. Its SAM solvent is butyrolactone with a concentration of 15 μg / ml. Heat it to different temperatures of 150 °C, 180 °C, 210 °C, 240 °C, and 270 °C respectively, and then quickly immerse the cleaned (ultrasonic cleaning for 20 minutes in the order of acetone, IPA, acetone, IPA, drying at 65 °C, and ultraviolet ozone treatment for 15 minutes) conductive glass substrate into the SAM solutions at the above different temperatures for 5 seconds. Then quickly transfer and immerse it into the SAM butyrolactone solution with the same formula at room temperature for 10 s, take it out and dry it with a nitrogen gun, anneal it in air at 110 °C for 10 minutes, cool it to room temperature and then transfer it to the glove box. Then, mix CsI, FAI, MABr, MACl, PbBr2 and PbI2 in a DMF:DMSO mixed solvent (4:1 v:v) to prepare a 1.4 M perovskite precursor solution with the chemical formula Cs 0.05 MA 0.05 FA 0.90 PbBr0.1 I 2.9 . Before deposition, 10 mol% MACl, 1 mg / ml GuaBCl, 1 mg / ml PMACl and 2 mg / ml PbCl2 were added to the perovskite precursor, stirred for more than 6 hours and then transferred to a spin coater. 65uL of the precursor was dropped on the SAM substrate, spin coated at 1000rpm for 5 seconds, 5000rpm for 30 seconds, and 120μL of chlorobenzene was added as an antisolvent within the last 15 seconds. The perovskite film was then annealed at 110°C for 20 minutes. For surface passivation, the solvent used was 3mg / ml PDADI, 0.5mg / ml MDAI2 and 0.5mg / ml FAI dissolved in a mixed solvent of IPA and DMSO (IPA:DMSO=99:1v:v). The passivation solvent was spin coated on the perovskite film at 5000rpm for 20 seconds and then annealed at 110°C for 10 minutes. The film was transferred to a thermal evaporator and heated under high vacuum (<5×10 -5 LiF, C were deposited at a thickness of 2.5 nm, 18 nm, 4.5 nm, and 80 nm, respectively. 60 , BCP and Cu.

[0068] Example 2

[0069] This embodiment provides a perovskite solar cell, which differs from Embodiment 1 only in that the solvent of SAM is N,N-dimethylformamide (DMF), the immersion temperatures are 150°C, 180°C, 210°C, 240°C, and 270°C, respectively, and the other materials, structures, and preparation methods are the same as those in Embodiment 1.

[0070] Example 3

[0071] This embodiment provides a perovskite solar cell, which differs from Embodiment 1 only in that the solvent of SAM is n-butanol, the immersion temperatures are 180°C, 210°C, 240°C, 270°C, and 300°C, respectively, and other materials, structures, and preparation methods are the same as those in Embodiment 1.

[0072] Example 4

[0073] This embodiment provides a perovskite solar cell, which is different from the embodiment 3 only in that the solvent of SAM is n-butanol, and the immersion temperature is only 270° C. Other materials, structures and preparation methods are the same as those of the embodiment 3.

[0074] Comparative Example 1

[0075] This embodiment provides a perovskite solar cell, which differs from Embodiment 4 only in that the solvent of SAM is ethanol, the concentration of SAM molecules is 0.75 mg / ml, and it is obtained by spin coating at a speed of 5000 rpm for 30 seconds, then annealing in air at 110°C for 10 minutes, and then transferring to a glove box for the remaining steps. Other materials, structures and preparation methods are the same as those in Embodiment 4.

[0076] Performance Testing

[0077] The open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and initial photoelectric conversion efficiency (PCE) of the perovskite cells provided in Examples 1 to 4 and Comparative Example 1 were tested; the test results are shown in Table 1.

[0078] In addition, taking Example 4 and Comparative Example 1 as examples, the long-term stability of the perovskite battery was tested. The battery in Example 4 and the battery in Comparative Example 1 were stored at room temperature and in the dark, and their performance was tested at regular intervals. The results are as follows: Figure 5 As shown, it can be seen that the conversion efficiency of the perovskite battery provided by the present invention decays little with the extension of time, and the conversion efficiency can still reach more than 90% of the initial conversion efficiency after 3900 hours; while the comparative example 1 can only reach about 60% of the initial conversion efficiency, which proves that the perovskite battery provided by the present invention has better stability and longer service life.

[0079] Table 1

[0080] Voc(V) Jsc(mAcm-2) FF PCE(%) Example 1 1.199±0.049 24.95±0.1251 0.8273±0.0087 24.75±0.101 Example 2 1.198±0.044 24.96±0.09 0.8170±0.0042 24.43±0.11 Example 3 1.2±0.04 24.98±0.10 0.8260±0.005 24.76±0.092 Example 4 1.208±0.0036 24.97±0.039 0.8367±0.0039 25.35±0.137 Comparative Example 1 1.192±0.0044 24.88±0.027 0.8179±0.0034 24.26±0,081

[0081] As can be seen from Table 1, the perovskite cell provided by the present invention, by using the above-mentioned high-throughput in-situ deposition technology to prepare a denser and more uniform SAM layer, greatly reduces the leakage current of the buried interface of the perovskite cell, significantly reduces the interface recombination, and at the same time, the higher quality SAM layer also contributes to the growth of perovskite crystals, resulting in larger grains, better buried interface contact, and reduced buried interface defects, so the stability of the battery is also greatly improved.

[0082] In the present invention, the conversion efficiency of the single-junction perovskite solar cell based on the SAM layer reaches 25.68%, and after storage for 3900 hours, the conversion efficiency can still reach more than 90% of the initial value; compared with the conversion efficiency of comparative example 1 of only 24.41%, after storage for 3900 hours, the conversion efficiency has dropped to less than 90%. The efficiency and service life of the perovskite battery provided by the present invention are significantly improved.

[0083] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a self-assembled monolayer in a perovskite battery, characterized in that: The steps include: Step S1, preparing a SAM layer; Step S1.1, immersing the conductive glass substrate into the preheated SAM first precursor solution; Step S1.2, quickly immersing in the second SAM precursor solution; Step S1.3, taking out and removing the residual solvent to obtain a SAM layer; Step S2, annealing; Step S3, preparing a perovskite light absorbing layer and other functional layers; Sequentially depositing a perovskite light-absorbing layer and other functional layers on the SAM layer to ultimately prepare a complete perovskite solar cell; The solvents of the first SAM precursor liquid and the second SAM precursor liquid are both high boiling point solvents; The perovskite light-absorbing layer is any organic-inorganic metal halogen hybrid perovskite light-absorbing material; The other functional layers include a perovskite surface passivation layer, an electron transport layer, an interface modification layer and an electrode.

2. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The raw materials of the first SAM precursor solution and the second SAM precursor solution are both small molecule materials having a phosphate group and a function of modifying the interface of perovskite / conductive substrate, including but not limited to MeO-2PACz, [3-(3,6-dimethoxy-9H-carbazole-9-yl)propyl]phosphate (MeO-3PACz), [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphate (MeO-6PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphate (Me-2PACz), [3-(3,6-dimethyl-9H-carbazole-9-yl)propyl]phosphate (Me ...methyl-9H-carbazole-9-yl)hexyl]phosphate (MeO-6PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphate (Me-6PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphate (Me-6PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphate (Me-6PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphate (Me-6PACz), [6-(3,6-dimethyl-9H-carbazole-9-yl)hexyl]phosphate (Me-6PACz), )hexyl] phosphate (Me-6PACz), [1-(3,6-dimethyl-9H-carbazol-9-yl)methyl] phosphate (Me-1PACz), [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl] phosphate (Me-4PACz), [8-(3,6-dimethyl-9H-carbazol-9-yl)octyl] phosphate (Me-8PACz), [1-(9H-carbazol-9-yl)methyl] phosphate (1PACz), (2-(9H-carbazol-9-yl)ethyl) phosphate (2PACz), [3-(9H-carbazol-9-yl)propyl] phosphate (3PACz), [4-(9H-carbazol-9-yl)butyl] phosphate (4PACz), [6-(9H-carbazol-9 2-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)ethyl] phosphate (2PABCz), [4-(9H-9'-phenyl-3,3'-dicarbazole-9-yl)butyl] phosphate (4PABCz), [4-(diphenylamino)phenyl)ethyl] phosphate (TPA-2PA), [4-(diphenylamino)phenyl)propyl] phosphate (TPA-3PA), [4 -(10H-phenothiazine-10-yl)butyl]phosphoric acid (4PAPT), [2-(7H-dibenzocarbazole-7-yl)ethyl]phosphoric acid (2PADCB), [4-(7H-dibenzocarbazole-7-yl)butyl]phosphoric acid (4PADCB), [3-(3,6-dibromo-9H-carbazole-9-yl)propyl]phosphoric acid (2Br-3PACz), [4-(3,6-dibromo-9H-carbazole-9-yl)butyl]phosphoric acid (2Br-4PACz), [6-(3,6-dibromo-9H-carbazole-9-yl)hexyl]phosphoric acid (2Br-6PACz), [1-(3,6-di-tert-butyl-9H-carbazole-9-yl)methyl]phosphoric acid (tBu-1PACz), [2 ...[6-di-tert-butyl-9H-carbazole-9-yl)ethyl] phosphate (tBu-2PACz), [3-(3,6-di-tert-butyl-9H-carbazole-9-yl)propyl] phosphate (tBu-3PACz), [4-(3,6-di-tert-butyl-9H-carbazole-9-yl)butyl] phosphate (tBu-4PACz), [6-(3,6-di-tert-butyl-9H-carbazole-9-yl)hexyl] phosphate (tBu-6PACz), [8-(3,6-di-tert-butyl-9H-carbazole-9-yl)octyl] phosphate (tBu-8PACz), [1-(3,6-diphenyl-9H-carbazole-9-yl)methyl] phosphate (Ph-1PACz), [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl] phosphate (Ph-2PACz), [3 -(3,6-diphenyl-9H-carbazole-9-yl)propyl] phosphate (Ph-3PACz), [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl] phosphate (Ph-4PACz), [6-(3,6-diphenyl-9H-carbazole-9-yl)hexyl] phosphate (Ph-6PACz), [8-(3,6-diphenyl-9H-carbazole-9-yl)octyl] phosphate (Ph-8PACz), [2-(10H-phenoxazine-10-yl)ethyl] phosphate (2PAPXZ), [4-(3,7-dibromo-10H-phenothiazine-10-yl)butyl] phosphate (2Br-4PAPT), [4-(3,7-dibromo-10H-phenoxazine-10-yl)butyl] phosphate (2Br-4PAPXZ) and a series of phosphate molecules. , 3. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The solvents of the first SAM precursor solution and the second SAM precursor solution are both solvents with polarity>3.0, including but not limited to isobutanol, n-butanol, butyl acetate, propanol, methyl isobutyl ketone, tetrahydrofuran, ethyl acetate, isopropanol, chloroform, methyl ethyl ketone, dioxane, pyridine, acetone, nitromethane, acetic acid, acetonitrile, aniline, dimethylformamide, methanol, ethylene glycol, dimethyl sulfoxide, ethanol, butyrolactone, water, etc. The solvents of the first SAM precursor solution and the second SAM precursor solution also include a combination of any type and ratio of two or more of the above solvents.

4. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The concentration range of the first SAM precursor solution is 1ug / mL-1000ug / mL, the concentration range of the second SAM precursor solution is 1ug / mL-100ug / mL, the temperature of the first SAM precursor solution is 60°C-300°C, and the temperature range of the second SAM precursor solution is 0°C-200°C.

5. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The immersion time of the conductive glass substrate in the first SAM precursor solution is 0.5 seconds to 300 seconds, the immersion time of the conductive glass substrate in the second SAM precursor solution is 5 seconds to 1800 seconds, and the time of transferring from the first SAM precursor solution to the second SAM precursor solution is <2 seconds.

6. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: After the conductive glass substrate is taken out from the second precursor solution, residual solvent is removed. Methods for removing the residual solvent include but are not limited to strong drying with nitrogen, drying with argon, drying with dry compressed air, drying with carbon dioxide gas, drying with infrared lamp, vacuum drying, etc.

7. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: After the conductive glass is taken out from the second precursor solution, residual solvent is removed and annealed. The annealing temperature is 80° C.-200° C., the annealing time is 1 minute-30 minutes, and the annealing environment is in an air environment or in a glove box protected by an inert gas.

8. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The perovskite light absorbing layer and other functional layers are deposited on the SAM layer at one time, and the methods of depositing the perovskite and other functional layers include but are not limited to spin coating, scraping, slit coating, screen printing, thermal evaporation, ion beam deposition, magnetron sputtering deposition, atomic layer deposition, etc.

9. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The general structural formula of the material of the perovskite light absorbing layer is ABX3; Wherein, A is selected from CH3NH3 + (MA + )、CH(NH2)2 + (FA + ), Rb + or Cs + Any one or a combination of at least two of the following: B is selected from Pb 2+ ,Ge 2+ Sn 2+ Any one or a combination of at least two of the following: X is selected from Cl - Br - or I - Any one or a combination of at least two of the following: The thickness of the perovskite light absorbing layer is 200nm to 1500nm; The perovskite cell types include single-cell perovskite solar cells and also include the hole collection layer of the broadband perovskite part in the perovskite / crystalline silicon stacked solar cell.

10. The method for preparing a self-assembled monolayer in a perovskite battery according to claim 1, characterized in that: The perovskite cell types include perovskite / perovskite stacked solar cells, which serve as hole transport layers for wide bandgap and narrow bandgap cells, respectively.

Citation Information

Cited By

  • Interface optimization perovskite solar cell and preparation method thereof

    CN119836102A

  • Method for preparing perovskite solar cell based on interface modification

    CN120379497A

  • A preparation method of perovskite solar cell based on interface modification

    CN120379497B

  • Preparation method of perovskite solar cell based on hole transport layer

    CN120379498A

  • A method for preparing a perovskite solar cell based on a hole transport layer

    CN120379498B